2021
DOI: 10.1111/jomf.12808
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between sibling relationship quality and child adjustment after divorce

Abstract: Objective This study examined the interplay between the parent–child and sibling relationships in their associations with child adjustment after divorce, in order to understand the postdivorce impact of the sibling relationship more thoroughly. Background The sibling relationship is unique in its lifetime duration and frequent interactions, and is associated with child adjustment in intact families. Research on the sibling relationship in divorced families is warranted, as it is one of the few stable factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 90 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…More specifically, sibling hostility is positively associated with higher levels of depressive symptoms ( Campione-Barr et al, 2013 ), difficulties with peers, problems at school, and substance use ( Odudu et al, 2020 ). At the same time, siblings are an important source of emotional support ( Johnson and Salafia, 2022 ), and sibling affection is not only positively correlated with adolescents’ satisfaction with life and emotional wellbeing ( Padilla-Walker et al, 2010 ; Harper et al, 2016 ) but also associated with lower instances of behavioral problems, including depressive symptoms and aggression ( Branje et al, 2004 ; van Dijk et al, 2022 ). Thus, sibling relationships may mediate the connection between marital relationships and adolescent behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, sibling hostility is positively associated with higher levels of depressive symptoms ( Campione-Barr et al, 2013 ), difficulties with peers, problems at school, and substance use ( Odudu et al, 2020 ). At the same time, siblings are an important source of emotional support ( Johnson and Salafia, 2022 ), and sibling affection is not only positively correlated with adolescents’ satisfaction with life and emotional wellbeing ( Padilla-Walker et al, 2010 ; Harper et al, 2016 ) but also associated with lower instances of behavioral problems, including depressive symptoms and aggression ( Branje et al, 2004 ; van Dijk et al, 2022 ). Thus, sibling relationships may mediate the connection between marital relationships and adolescent behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effects of divorce on sibling relationships show a big variation in how children, as a family subsystem, cope with changes in the family [11]. It is emphasized that relations with siblings are among those few factors in children's lives during the divorce and shortly after the divorce and complement the relations with parents [12]. The consequences of divorce stem not only from the separation of the child from the parent but also from the family malfunctioning before the divorce and/or difficult living conditions and conflicts after the divorce (e.g., on the level of parental cooperation) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the sibling relationship can be characterized by conflict and aggression (Tucker & Finkelhor, 2017), it is also one of the closest, most enduring emotional bonds throughout life (Buhrmester & Furman, 1990;Volling, 2003). In fact, some studies suggest that siblings may turn to one another for affection and support in an effort to compensate for negativity in their caregivers' relationship (van Dijk et al, 2021) and that siblings can play a supportive role and act as a buffer in other stressful family contexts (Gass et al, 2007;Sanner et al, 2023). For example, Gass et al (2007) found sibling affection moderated the stressful life events on internalizing behaviors in siblings 5 to 17 years old in an English sample.…”
mentioning
confidence: 99%
“…In the mid‐1980s, researchers began to examine the quality of sibling relationships (Furman & Buhrmester, 1985b). Since then, some researchers examined sibling relationship quality among siblings where one sibling has a disability such as autism (Walton & Ingersoll, 2015) or a major health condition such as cancer (Cheung et al., 2020), and other researchers have focused on sibling relationship quality among siblings with shared experiences, such as parental divorce or foster care involvement (van Dijk et al., 2021; Wojciak et al., 2018). However, many of the sibling relationship quality studies have utilized general population sibling samples to understand what predicts sibling relationship quality (e.g., Kramer & Baron, 1995; Ruff et al., 2018) or what type of sibling relationship qualities predicts child well‐being outcomes (e.g., Finan et al., 2018; Gamble & Modry‐Mandell, 2008; Richmond et al., 2005).…”
mentioning
confidence: 99%